Systematic versus on-demand early palliative care: A randomised clinical trial assessing quality of care and treatment aggressiveness near the end of life. (December 2016) - Maltoni, Marco; Scarpi, Emanuela; Dall'Agata, Monia; Schiavon, Stefania; Biasini, Claudia; Codecà, Carla; Broglia, Chiara Maria; Sansoni, Elisabetta; Bortolussi, Roberto; Garetto, Ferdinando; Fioretto, Luisa; Cattaneo, Maria Teresa; et al.
Abstract: Aim: Early palliative care (EPC) in oncology has shown sparse evidence of a positive impact on patient outcomes, quality of care outcomes and costs. Patients and methods: Data for this secondary analysis were taken from a trial of 207 outpatients with metastatic pancreatic cancer randomly assigned to receive standard cancer care plus on-demand EPC (standard arm) or standard cancer care plus systematic EPC (interventional arm). After 20 months' follow-up, 149 (80%) had died. Outcome measures were frequency, type and timing of chemotherapy administration, use of resources, place of death and overall survival. Results: Some indices of end-of-life (EoL) aggressiveness had a favourable impact from systematic EPC. Interventional arm patients showed higher use of hospice services: a significantly longer median and mean period of hospice care ( P = 0.025 for both indexes) and a significantly higher median and mean number of hospice admissions (both P < 0.010). In the experimental arm, chemotherapy was performed in the last 30 days of life in a significantly inferior rate with respect to control arm: 18.7% versus 27.8% (adjusted P = 0.036). Other non-significant differences were seen in favour of experimental arm. Conclusions: Systematic EPC showed a significant impact on some indicators of EoL treatment aggressiveness. These data, reinforced by multiple non-significant differences in most of the other items, suggest that quality of care is improved by this approach. This study is registered onClinicalTrials.gov (NCT01996540 ). Highlights: We assessed the impact of systematic versus on-demand early palliative care (EPC) on quality of care outcomes. Use and timeliness of hospice care were more appropriate in the systematic EPC arm. Fewer systematic EPC patients underwent chemotherapy in the last 30 days of life. Percentage of home/hospice deaths was non-significantly higher for systematic EPC. Systematic EPC is advantageous for quality of care and quality of life.